Pengaruh E-Recruitment, Reputasi Perusahaan, dan Kompensasi Terhadap Minat Melamar Kerja Kajian Ekonomi Islam (Studi Pada Fresh Graduate di Semarang) - Hayomi, Yuliana Aise; Suharnomo, Suharnomo (Jurnal Ilmiah Ekonomi Islam, 2024)
Recruitment is a company's source of obtaining competent human resources, along with this, interest in applying for jobs is a topic that is closely related to recruitment success. This research aims to determine e-Recruitment, compensation and company reputation on interest in applying for jobs. The population in this study were fresh graduates in Semarang City, totaling 115 samples using non-probability sampling with a purposive sampling method. Data collection method using a questionnaire given to the research sample. Path analysis was used in this research with the help of IBM SPSS Version 20 software. The results in this research show that e-Recruitment, compensation and company reputation. The results of this research suggest companies to implement e-Recruitment. Companies are also advised to pay attention to their reputation. Next, companies need to pay attention to the compensation offered. It is hoped that future research will be able to use the information obtained to be more relevant. Apart from that, future researchers are also advised to further examine other variables that influence interest in applying for jobs according to previous research.